Circuit design of VLSI for microelectronic coordinate-sensitive detector for material element analysis - Sidorenko, V. P.; Verbitskii, V. G.; Prokofiev, Yu. V. (Technology and design in electronic equipment, 2012)
There has been designed, manufactured and tested a VLSI providing as a part of the microelectronic coordinate-sensitive detector the simultaneous elemental analysis of all the principles of the substance. VLSI ensures the amplifier-converter response on receiving of 1,6.10–13 С negative charge to its input. Response speed of the microcircuit is at least 3 MHz in the counting mode and more than 4 MHz in the counter information read-out mode. The power consumption of the microcircuit is no more than 7 mA.